1999
DOI: 10.1016/s0741-5214(99)70362-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage after carotid endarterectomy: Incidence, contribution to neurologic morbidity, and predictive factors

Abstract: Intracranial hemorrhage occurs with notable frequency after carotid endarterectomy and accounts for a significant proportion of neurologic morbidity and mortality. Younger patients, hypertensive patients, and patients with severe cerebrovascular occlusive disease appear to be at greatest risk for the complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 14 publications
5
102
1
6
Order By: Relevance
“…The headache in CHS is usually moderate to severe and throbbing, similar to a migraine headache (Coutts et al, 2003), and it usually affects the same side as the artery treated. Headache may be the only manifestation of CHS (Connolly 2000;Ouriel et al, 1999;Sbarigia et al, 1993), so occasionally it has been considered a diagnostic criterion. After CEA, headaches are reported in 20% of patients without CHS, in 59% of those with CHS, and in 84% of those with ICH (Bouri et al, 2011).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…The headache in CHS is usually moderate to severe and throbbing, similar to a migraine headache (Coutts et al, 2003), and it usually affects the same side as the artery treated. Headache may be the only manifestation of CHS (Connolly 2000;Ouriel et al, 1999;Sbarigia et al, 1993), so occasionally it has been considered a diagnostic criterion. After CEA, headaches are reported in 20% of patients without CHS, in 59% of those with CHS, and in 84% of those with ICH (Bouri et al, 2011).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…After CEA, headaches are reported in 20% of patients without CHS, in 59% of those with CHS, and in 84% of those with ICH (Bouri et al, 2011). Postprocedural hypertension is a critical, though not essential, finding associated with CHS Schroeder et al, 1987;Ouriel et al 1999). Bouri et al review (2011) found that the mean systolic BP of CHS cases was 189 mmHg at presentation, and the proportion of patients with severe hypertension was significantly higher in patients who developed CHS after CEA than in those who did not.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations